-8x+24=-8(6+4x)

Simple and best practice solution for -8x+24=-8(6+4x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8x+24=-8(6+4x) equation:


-8x+24=-8(6+4x)

We simplify the equation to the form, which is simple to understand
-8x+24=-8(6+4x)

Reorder the terms in parentheses
-8x+24=+(-48-32x)

Remove unnecessary parentheses
-8x+24=-48-32x

We move all terms containing x to the left and all other terms to the right.
-8x+32x=-48-24

We simplify left and right side of the equation.
+24x=-72

We divide both sides of the equation by 24 to get x.
x=-3

See similar equations:

| 2(5x-5)=10(x-5) | | 3/20-4/5= | | 2a-11=-23 | | 5g+3(-4+3g)=1-g | | 5a^3-31a-28=0 | | 54x^3=6x | | v^2=-45-14v | | 0.5*y=14 | | -10b^2-(-9b^2-4)= | | 5(1-9a)=35 | | 3z+8+(-2z)=12 | | (x+2)*(x-6)-6=0 | | 2x^24=y | | 11k=264 | | 3/20-4/5-3/4= | | 2x+9=3(-7-2x) | | (kn)*m= | | 6a-9=15 | | -4+21a=10-2a | | 12+5(v)=2(v)-9 | | 14x+6=10+14x-4 | | 0.60x+0.60(60)=0.30(118) | | -9.2(x-3.5)=36.8 | | 2x^2+x^3y^4=1 | | 4(x-8)+7=11x-15 | | 3(6x+7)-9=18x+12 | | 3(1-5x)=x+19 | | 3r+2s-4t=-24 | | 11x-7x=36 | | 8x+4=x+20 | | 72d-45+13=12d-2 | | 91x^3+8x+9x^2= |

Equations solver categories